Al-Hijaj Al-Badiee in the Book of Al – Kashkool For Al – Sheikh Al – Bahaee (Date: 1030 A.H.) - Saddam Shati, Maitham; Al–Musawi, Ahmed Batal Waseej (Al-Adab Journal, 2020)
The addressee studies this research which is Al-Hijaj Al-Badiee in the texts of Book of Al – Kashkool For Al – Sheikh Al – Bahaee in order to explain the effect of Al-Hijaj Al-Badiee on strengthening the rule that the speaker wants and support his argument and refute the opinion The research consisted of a preamble and three topics. The preamble is presented by introduction in Al – Badiee, to state the meaning of Al – Hijaj Al – Badiee, its effect on persuading the recipient. First research under title (Alliteration & Assonance) to state impact of these two arts to enrich Al – Hijaj Al – Badiee. Second research under title (Repetition) to clarify its two types (Word – Sentence), effect of these two categories to present Al – Hijaj Al – Badiee. Third research was under title (Counterpoint & Encounter) to study positions of these two arts in the book of Al – Kashkool and their effect to make Al – Hijaj Al – Badiee prominent The research concluded many results like that Rhetorical Al – Hijaj is not restricted on statement only through (Metaphor, Representation) but also this Al – Hijaj is founded within significant sides of various arts of Al – Badiee. Moreover Al – Bahaee has used more of arts of Al – Badiee as an example the voice dominant, particularly Anagrams, assonance, its linking with semantic of meaning which was to be affirmed by thought of Al – Hijaj. Such as used art of repetition which collects between sound, semantic. its texts confirmed that work to strengthen thought of Al – Hijaj. where Al – Bahaee has used more of semantic of two arts of counterpoint, encountering in his writings where these two arts affected to support pretext of the speaker and his proof.